2005
DOI: 10.1038/sj.npp.1300807
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin/Orexin Selectively Increases Dopamine Efflux within the Prefrontal Cortex: Involvement of the Ventral Tegmental Area

Abstract: Hypocretins (HCRTs) modulate a variety of behavioral and physiological processes, in part via interactions with multiple ascending modulatory systems. Further, HCRT efferents from the lateral hypothalamus innervate midbrain dopamine (DA) nuclei, and DA cell bodies express HCRT receptors. Combined, these observations suggest that HCRT may influence behavioral state and/or statedependent processes via modulation of DA neurotransmission. The current studies used in vivo microdialysis in the unanesthetized rat to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
114
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 67 publications
7
114
0
1
Order By: Relevance
“…However, the relative financial expense and the lack of bioavailability of orexin-A coupled with drastically different potency when injected i.v. versus centrally (Kiyashchenko et al, 2001;Vittoz and Berridge, 2006) has precluded systemic orexin-A as a candidate for controlling the effects of sleep deprivation (Hara et al, 2001). We show here that these limitations can be greatly overcome by delivering orexin-A via nasal spray which proved superior to systemically delivered orexin-A both in terms of enhancing performance in sleep-deprived monkeys as well as reversing the effects on altered CMRglc levels in key brain areas affected by sleep deprivation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the relative financial expense and the lack of bioavailability of orexin-A coupled with drastically different potency when injected i.v. versus centrally (Kiyashchenko et al, 2001;Vittoz and Berridge, 2006) has precluded systemic orexin-A as a candidate for controlling the effects of sleep deprivation (Hara et al, 2001). We show here that these limitations can be greatly overcome by delivering orexin-A via nasal spray which proved superior to systemically delivered orexin-A both in terms of enhancing performance in sleep-deprived monkeys as well as reversing the effects on altered CMRglc levels in key brain areas affected by sleep deprivation.…”
Section: Discussionmentioning
confidence: 80%
“…Receptors for orexin-A are located on neurons in many different brain regions making it possible for this peptide, once released, to activate a large number of areas affected by sleep and sleep deprivation (Hagan et al, 1999;Bourgin et al, 2000;Kilduff and Peyron, 2000;Piper et al, 2000;Gerashchenko et al, 2001;Yoshida et al, 2001;Wu et al, 2002;Peever et al, 2003;Lee et al, 2005;Mileykovskiy et al, 2005;Vittoz and Berridge 2006), It has recently been shown that manipulation of this system via administration of a orexin antagonist can increase sleep in rats, dogs and humans (Brisbare-Roch et al, 2007). The loss of orexin cells has been shown to cause human and animal narcolepsy (Chemelli et al, 1999;Lin et al, 1999;Nishino et al, 2000;Peyron et al, 2000;Thannickal et al, 2000;Gerashchenko et al, 2001;Wu et al, 2002;Mieda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the effects of intra-VTA orexin on DA levels in the Acb has yielded mixed results. While some results suggest a link (53), others report that orexin action in the VTA results in increased prefrontal cortex DA levels with no change in Acb DA levels (54). Moreover, previous evidence suggests that the VTA may not play a role in morphine withdrawal.…”
Section: Discussionmentioning
confidence: 93%
“…Activity of A10 dopamine cells has been hypothesized to be important for enabling of motor, cognitive, and motivational behavior (Schultz, 1998;Datla et al, 2002) and may be one pathway by which endogenous orexin enhances arousal. Indeed, recent data have shown that orexin increases dopamine efflux in the PFC via activation of the VTA (Vittoz and Berridge, 2006). Thus, it could be hypothesized that orexin-1 receptor antagonists would block the effects of physiological stimulation (such as might occur during periods of arousal) of this pathway in the behaving animal.…”
Section: Discussionmentioning
confidence: 99%